2021
DOI: 10.3390/jcm10091864
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Its Impact on Urological Diseases and Management: A Comprehensive Review of the Literature

Abstract: Recent advances in artificial intelligence (AI) have certainly had a significant impact on the healthcare industry. In urology, AI has been widely adopted to deal with numerous disorders, irrespective of their severity, extending from conditions such as benign prostate hyperplasia to critical illnesses such as urothelial and prostate cancer. In this article, we aim to discuss how algorithms and techniques of artificial intelligence are equipped in the field of urology to detect, treat, and estimate the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 81 publications
0
37
0
1
Order By: Relevance
“…Artificial intelligence (AI) techniques can be used in that setting [ 23 ]. The applications of AI are vast [ 24 ], and include diagnostic imaging [ 25 ], pathology [ 26 ], segmentation [ 27 ], prognostics [ 28 ], and automatic treatment planning [ 29 , 30 ]. Our model is the first to be trained on a large, prospective, and multicenter cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) techniques can be used in that setting [ 23 ]. The applications of AI are vast [ 24 ], and include diagnostic imaging [ 25 ], pathology [ 26 ], segmentation [ 27 ], prognostics [ 28 ], and automatic treatment planning [ 29 , 30 ]. Our model is the first to be trained on a large, prospective, and multicenter cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…AI in PCa has been applied in different settings such as assessment of benign/malignant lesions, to distinguish significant versus non-significant cancer, defining active surveillance candidates, staging, prediction of response to treatment, and recurrence among others [ 46 , 47 , 48 , 49 , 50 ]. In terms of diagnosis, many studies have reported the advantages of different AI models to provide accurate diagnosis of PCa [ 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Mri and Artificial Intelligencementioning
confidence: 99%
“…The use of AI and ML has been studied in urology within the realm of urologic oncology, but also in other benign subspecialties, including endourology and pediatric urology [ 56 , 59 ]. However, one area that AI/ML may be applicable to all realms of urology is surgical training, particularly in robotic and microsurgical training.…”
Section: Artificial Intelligence Deep Learning and Machine Learningmentioning
confidence: 99%